2022
DOI: 10.1097/mao.0000000000003648
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation Outcomes in Patients With Retrocochlear Pathology: A Systematic Review and Pooled Analysis

Abstract: ObjectiveTo review the current literature regarding cochlear implantation in patients with retrocochlear pathologies and extract speech perception scores between 6 months and 1 year after surgery.Databases ReviewedPubMed/MEDLINE, Embase and Cochrane CENTRAL via Ovid, CINAHL Complete via Ebsco, and Web of Science.MethodsThe review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Search strategies included keywords and subject headings to maximize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…The reviews focused on outcomes in cochlear-implanted adults with tinnitus (Ramakers et al 2015; Peter et al 2019; Yuen et al 2021), Meniere disease (Desiato et al 2021; Selleck et al 2021; Villavisanis et al 2021), Usher syndrome (Davies et al 2021), vestibular schwannoma (Borsetto et al 2019; Schlacter et al 2022), and otosclerosis (Assiri et al 2022; Kondo et al 2023; Teaima et al 2023). Overall, CIs are generally safe and efficacious for these patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviews focused on outcomes in cochlear-implanted adults with tinnitus (Ramakers et al 2015; Peter et al 2019; Yuen et al 2021), Meniere disease (Desiato et al 2021; Selleck et al 2021; Villavisanis et al 2021), Usher syndrome (Davies et al 2021), vestibular schwannoma (Borsetto et al 2019; Schlacter et al 2022), and otosclerosis (Assiri et al 2022; Kondo et al 2023; Teaima et al 2023). Overall, CIs are generally safe and efficacious for these patients.…”
Section: Resultsmentioning
confidence: 99%
“…For other retrocochlear pathologies, 82% of the 171 adults included in the review by Schlacter et al (2022) demonstrated improvements in speech perception 6 months to 1 year after implantation with change in consonant-nucleus-consonant word scores ranging from 25.6 to 78% and change in AzBio sentences scores ranging from 36.5 to 51%. In adults with otosclerosis, Assiri et al (2022) reviewed 21 studies with extractable data (n = 2 to 36) and showed that all studies reported audiological improvement postimplantation.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…19,35,49 In more than half the patients with good postimplantation performance and stable tumors, hearing was preserved for long periods, consistent with published findings. 35,38,50,51 In meta-analyses considering the prognostic factors for speech intelligibility, the NF2 population has generally been split into 2 categories: good-to-intermediate performers (34%-100%) and poor performers (0%-33%). 19,49 The prognostic factors for poor performers have not fully been clarified, although some authors have reported associations between poor performance and large tumors, a shorter duration of profound HL, and lower preimplantation audiometric scores.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains challenging to confirm the presence of a functionally intact cochlear nerve before or during surgery 31 . Given the rarity of NF2, most of the studies performed include only limited numbers of patients or a mixture of patients with sporadic and NF2‐related VS, leading to discrepancies in the results obtained 19,37,38 . Moreover, little is known about long‐term hearing outcomes in NF2 patients.…”
mentioning
confidence: 99%
“…Studies meeting overall appraisal criteria for inclusion using the Joanna Briggs Institute Critical Appraisal Checklist and the Cochrane Risk of Bias Assessment Tool were included and are listed in Table 2 (11)(12)(13)(14)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) with their respective Oxford Level of Evidence (15,16). Eighty-eight articles were excluded after full text review (Supplemental Content: Appendix Table 1, http://links.lww.com/MAO/ B815).…”
Section: Systematic Reviewmentioning
confidence: 99%